2007
DOI: 10.1371/journal.pone.0001194
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Vipera aspis Venom Neurotoxicity

Abstract: BackgroundThe variation of venom composition with geography is an important aspect of intraspecific variability in the Vipera genus, although causes of this variability remain unclear. The diversity of snake venom is important both for our understanding of venomous snake evolution and for the preparation of relevant antivenoms to treat envenomations. A geographic intraspecific variation in snake venom composition was recently reported for Vipera aspis aspis venom in France. Since 1992, cases of human envenomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 38 publications
5
44
1
3
Order By: Relevance
“…Intravascular hemolysis might also occur, in some cases associated with microthrombi formation (Warrell, 1996). Exceptions to this general trend are envenomings by the South American and some populations of North American rattlesnakes, as well as some viperids in the Old World, which induce neurotoxicity (AzevedoMarques et al, 2009;Ferquel et al, 2007). Despite the existence of these general trends, clinical studies highlight the complexity of snakebite envenoming, as demonstrated by the description of 'unusual' manifestations in cases by some elapids in Asia and South America Manock et al, 2008;Trinh et al, 2010).…”
Section: Clinical Manifestations Of Envenomingmentioning
confidence: 99%
“…Intravascular hemolysis might also occur, in some cases associated with microthrombi formation (Warrell, 1996). Exceptions to this general trend are envenomings by the South American and some populations of North American rattlesnakes, as well as some viperids in the Old World, which induce neurotoxicity (AzevedoMarques et al, 2009;Ferquel et al, 2007). Despite the existence of these general trends, clinical studies highlight the complexity of snakebite envenoming, as demonstrated by the description of 'unusual' manifestations in cases by some elapids in Asia and South America Manock et al, 2008;Trinh et al, 2010).…”
Section: Clinical Manifestations Of Envenomingmentioning
confidence: 99%
“…The variation in venom composition and pharmacology has been addressed for different snake venoms at several levels (Chipppaux et al, 1991). Studies on understanding the intra-specific variability of venoms are gaining much attention with the intention of production of efficacious therapeutic antivenom and have been studied extensively (Goncalves, 1956;Glenn et al, 1983;Silveira et al, 1990;Yang et al, 1991;Lomonte and Carmona, 1992;Oguiura et al, 2000;Ferquel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Les régions de France les plus concernées sont les massif montagneux [2,6,10] et la Vendée [11]. Dans les années 1990, la prise en charge des patients envenimés par des vipères a été améliorée : élaboration d'un tableau de gradation corrélé aux quantités circulantes de venin [1,12,13] ; mise au point d'un antivenin purifié utilisable par voie intraveineuse et ayant prouvé lors d'essais cliniques une excellente tolérance [14] et une efficacité spectaculaire [15] ; découverte de plusieurs populations de vipères aspics neurotoxiques dans le Sud de la France [4,5] et en Italie [6,16]. L'antivenin Viperfav W est produit grâce à l'immunisation de chevaux contre le venin de trois espèces de vipères européennes dont Vipera ammodytes d'Europe de l'est et des Balkans.…”
Section: Discussionunclassified
“…Cependant, des travaux récents ont mis en évidence la présence dans le venin d'une vipère capturée à Font-Romeu de neurotoxines capables d'interagir avec des anticorps antiammoditoxines. Cela amenait les auteurs à prévoir l'observation d'envenimations avec neurotoxicité dans les Pyrénées [6], ce qui est désormais confirmé par notre observation. Tous les travaux publiés font état d'une efficacité du Viperfav W sur les symptômes neurologiques [2,8].…”
Section: Discussionunclassified